Christian contribution to nation building - Sargunam, M. Ezra.; Jayakumar, Samuel; Ponraj, S. Devasagayam (Chennai : Mission Educational Books, 2006)
With reference to India.
"Compendium published on the occasion of Every Toungue and Tribe Festival, Chennai, January, 2006."
Keywords: Christianity -- Social aspects -- India; Christianity and politics -- India; India -- Church history